Lagged Relationships Among Chemotherapy-Induced Peripheral Neuropathy, Sleep Quality, and Physical Activity During and After Chemotherapy. Issue 9 (16th November 2020) - Bulls, Hailey W; Hoogland, Aasha I; Small, Brent J; Kennedy, Brittany; James, Brian W; Arboleda, Bianca L; Shahzad, Mian M K; Gonzalez, Brian D; Jim, Heather S L
Abstract: Background: Chemotherapy-induced peripheral neuropathy (CIPN) is well-documented and can become chronic for up to a third of patients. CIPN management is hampered by limited pharmacological options. Thus, identifying modifiable behaviors that influence CIPN may help inform future interventions. Purpose: The purpose of the current study was to examine bidirectional relationships between sleep quality, physical activity, and CIPN during and after chemotherapy. Methods: Participants were 138 women with gynecologic cancer ( M age = 61, 94% white, 96% non-Hispanic), collected as part of an ongoing study. Assessments occurred at postcycle 1, postcycle 6, and 6- and 12-month postchemotherapy. CIPN (EORTC-CIPN20), sleep quality (PSQI), and physical activity (IPAQ) were assessed via self-report. Objective physical activity was assessed via wrist actigraphy. Latent change score models were used to examine lagged relationships between CIPN, sleep quality, and physical activity pairs. Results: Over the study period, sleep quality was found to contribute to CIPN ( p = .001), but not the reverse ( p > .05). Bidirectional relationships were observed between CIPN and both objective and subjective walking ( p s ≤ .001). Illustrations of these relationships showed that patients with less CIPN early in treatment demonstrate more substantial increases in walking over time, while those with higher CIPN demonstrate more consistent levels of walking during and after treatment. Conclusions: These findings suggest that worse sleep quality and lower walking levels may contribute to the course and maintenance of CIPN. Future investigation should evaluate the impact of early interventions aimed at improving sleep quality and encouraging physical activity in patients treated with chemotherapy. Abstract : Chemotherapy-induced peripheral neuropathy during treatment and in the year post-chemotherapy is worse among patients with poor sleep quality and low walking levels